Mechanical and Microstructural Characterization of Hybrid Composite Developed By Compression Molding - Sukur, Mohammad Ariff (Universiti Teknologi PETRONAS, 2008)
Hybrid composites are developed usmg compression molding machine. The developed hybrid composite consists of a matrix material with a combination of 2 fiber reinforcements. There are 3 types of fiber reinforcements used in this study which are the woven glass, carbon and Kevlar fibers. The matrix materials used are either epoxy or polyester. The developed hybrid composite consists of fiber contents ranging from 15% to 45%. For polyester based composite, it is cured at room temperature while for epoxy based composite, it was cured at a temperature of 80°C. Both of the composite types were tested for its mechanical properties which are the tensile test and impact test. Then, the microstructural structure of the developed hybrid composite is analyzed. Results showed that the tensile strength increases with the fiber volume concentration. Hybrid composite reinforced with Kevlar and glass possesses high impact properties compared to the hybrid composite reinforced with carbon and glass fiber. The Microstructural analysis showed that impact resulted in brittle fracture in the case of carbon and glass fibers. While the Kevlar fibers show a ductile type of fracture.